Values and Prostitution: A Critical Exploration - Balogun, Noah Opeyemi (African Journal of Stability and Development (AJSD), 2018)
Considering the fact that values are themselves harbingers of confusion, because of the fleeting meaning they evince in different people, passing value judgment especially on an activity that bothers on how people define themselves and in fact, interpret their world, would be one of the most difficult tasks. Hence, this study examines values and value theories as they apply to the phenomenon and actual practice of prostitution. The debate between two schools of thought: the abolitionist which advocates an end to prostitution and, reformatory which aims at regulating prostitution is explored. Because value has to do with the study of human conduct, ethical questions bordering on prostitution are raised, and useful interjections are made with practical instances about the phenomenon and practices of prostitution. Using extant examples, the study argues that values are not immutable to socio-economic imperatives, and concludes that the question of values on prostitution is not yet fundamentally settled as the abolitionists and regulatory scholars would want.